Physical Properties of Flours Obtained from Wasted Bread Crusts and Crumbs - Juan Fernández-Peláez; Priscila Guerra; Cristina Gallego; Manuel Gomez (Foods, 2021)
One third of the food produced in the world is wasted. Bread is one of the most wasted foods both during the distribution process and in households. To use these breads, it is necessary to get to know the properties of the flours that can be obtained from them. The purpose of this work is to know how the type of bread and its zone (crumb or crust) influence the characteristics of the flours obtained from the wasted bread. For this, flours made from the crumbs and crusts of eight different breads have been analysed. Their hydration properties, cold and post-heating rheology and gelling properties as well as the colour of flours and gels have been studied. Bread flours present higher water-holding capacity (WHC) and water-binding capacity (WBC) values and higher elastic modulus (G’) and viscous modulus (G”) values, both in cold conditions and after heating, than wheat flours. However, they generate weaker gels. Crust flours, and the gels obtained from them, are darker than those from crumbs and their gels. In terms of hydration and rheology, pan and wholemeal bread flours are generally lower than other bread flours. These flours also generate softer gels, possibly caused by the dilution of starch with other components. It can be concluded that the properties shown by wasted bread flours allow them to be reintroduced in the food chain as an ingredient in different products.